Graphene Oxide: The Promising Potential in Dentistry: A Review - Hovhannisyan, S.; Mashinyan, K. A.; Torgomyan, A. L.; Hakobyan, G. (European Journal of Applied Sciences, 2023)
Objectives: In recent years the applications of graphene oxide (GO) have been extensively studied in various fields of medicine, due to its antibacterial properties and the ability to regenerate tissues. In dentistry, graphene oxide (GO) is also used to complement existing materials due to its unique properties, however, research on the use of graphene in dentistry is limited. What dictates a comprehensive review of the literature on the prospects for the use of graphene in clinical dentistry. In this review, we aim to highlight the potential of Graphene oxide, current understanding, and knowledge gaps regarding the antimicrobial behavior and biocompatibility of this materials. The purpose of this review article is to provide an overview of the use of graphene oxide (GO) in dentistry. Methods: Bibliographic databases PubMed, Embase, and Scopus were surveyed. The review focuses on the areas of application of Graphene oxide (GO) in dentistry, mainly based on a review of the most cited scientific papers in international peer-reviewed journals. Results: Graphene oxide (GO) has a unique structure and properties that differentiate it from other materials. Scope of application Graphene oxide (GO) broad in dentistry, it is used in prosthetics and restorative dentistry to optimize polymers and adhesives, dental implantology, to modify the surface of dental implants, to optimize the osteogenic properties of engineered tissue scaffolds through both surface and composite modifications, in periododntology and in endodontics thanks to his antimicrobial behavior. Conclusion: From this review, it can be concluded about the prospects for future developments, the use of Graphene in dentistry. Graphene oxide (GO) has the potential for future clinical applications in a variety of dental applications.